FUNCTIONAL AND PRAGMATIC ROLES OF PROVERBS IN ENGLISH AND GERMAN DISCOURSE COMMUNITIES - Shukurov Abbos Gulomovich; Olimov Avazbek Tursunpo’lot o’g’li (TADQIQOTLAR, 2025)
Annotation: This article explores the functional and pragmatic roles of proverbs in English and German discourse communities. Proverbs, as culturally embedded linguistic units, serve not only as carriers of collective wisdom but also as tools for persuasion, social regulation, and identity expression. The study analyzes how English and German speakers employ proverbs in everyday communication, institutional discourse, media, and literature. Attention is given to the pragmatic functions of proverbs such as argumentation, mitigation, strengthening claims, and establishing social solidarity. By comparing their use across the two linguistic and cultural contexts, the article highlights similarities rooted in shared European cultural heritage as well as differences influenced by historical, social, and cognitive factors. The findings contribute to a deeper understanding of how proverbs shape interpersonal interaction and cultural communication patterns.